Mémoires de Louise Michel écrits par elle-même. - Michel, Louise (Paris : Roy, 1886)
Collectie Vrijzinnige Werkmansbibliotheek
Frans
Monografie
Keywords: Michel, Louise; Vrijzinnige Werkmansbibliotheek